Drivers of Brand Loyalty in Food Delivery Applications: Evidence from India - Preeti Peter Ekka; Nutan Kumari (Journal of Enterprise and Development (JED), 2025)
Purpose: The advent of food delivery applications (FDAs) has markedly altered urban food consumption patterns, particularly within the Indian context. This study aims to investigate the primary factors that influence brand loyalty towards FDAs.Method: This research employs a quantitative methodology utilizing a cross-sectional survey design. Data were obtained from 400 urban consumers in the Raipur district of Chhattisgarh through meticulously constructed questionnaires, employing a 7-point Likert Scale. A purposive sampling technique was utilized, specifically targeting individuals who actively engage with FDAs. Structural Equation Modelling (SEM) was utilized for data analysis, employing Jamovi 2.6 software.Result: The findings indicated significant positive correlations among the examined variables. Customer Services and Ratings & Reviews demonstrated the most pronounced impact on Brand Loyalty, followed by Restaurant Selection and Delivery Time.Practical Implication for Economic Growth and Development: The results provide critical insights for marketers and application developers, enabling them to prioritize enhancements in customer service quality and effectively utilize ratings and reviews to augment user satisfaction and bolster customer retention on food delivery platforms.Originality/Value: This study represents one of the few empirical examinations focusing on urban consumers in the Raipur district of Chhattisgarh, contributing region-specific insights into the dynamics of consumer behavior and brand loyalty within the rapidly evolving Indian FDA market.